Pengaruh Kombinasi Expressive Writing dan Terapi Dzikir terhadap Smartphone Addiction dengan Kejadian Nomophobia pada Siswa Usia 10-14 Tahun Di SDN 2 Tungkaran Pangeran Tahun 2020 - dewy, tika sari (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2021)
Nomophobia is anxiety when away from a smartphone. Therapy that can be used to reduce nomophobia is writing therapy and dhikr therapy. One of the writing therapy used is expressive writing.Â  Expressive Writing is a writing activity that reflects individual reflection and expression which is personal, free of criticism, and language rules. Dhikr therapy is an activity of remembering Allah SWT with certain readings. The aim of this study was to determine the effect of the combination of expressive writing and dhikr therapy on smartphone addiction with nomophobia in students aged 10-14 years at SDN 2 Tungkaran Pangeran.The method of this study was quasi-experimental with one group without a control group pretest-posttest design. The sample was 33 respondents with a purposive sampling technique. The instrument of this study was Nomophobia Questionnaire.The results of this study indicated that there was an effect of a combination of expressive writing and dhikr therapy on scores and levels of nomophobia, the result of a statistical test by using the paired T-test obtained P-value 0,002 ( 0,05). The conclusion of this study, there was an effect of a combination of expressive writing and dhikr therapy on smartphone addiction with nomophobia in students aged 10-14 years at SDN 2 Tungkaran Pangeran in 2020. Suggestions for this study are expected to respondents aged 10-14 using a combination of expressive writing and therapy dzikir as an alternative to overcome nomophobia.